Pedagogical Care Ethics: Analysis of Mental Models in Caregiving Role Transformation Through Character Dialogues in the Film 1 Kakak 7 Ponakan - Lushinta, Istiqomah Putri; Syihabbudin, Syihabbudin; Zifana, Mahardhika (International Journal on Advanced Science, Education, and Religion, 2025)
This research analyzes the dynamics of care relationships and caregiving burden in extended families as represented in the film 1 Kakak 7 Ponakan directed by Yandy Laurens. The 129 minute film tells the story of Moko, an architecture student who must become the sole caregiver for his seven nieces and nephews after his sister and brother in law pass away, abandoning his dream of pursuing a master's degree at Columbia University. This study employs Cognitive Discourse Analysis (Van Dijk) integrated with care ethics (Gilligan, Noddings, Tronto) and pedagogical philosophy (Freire, Biesta) to explore mental models shaping caregiving discourse. Findings reveal three key aspects: (1) transformation from natural caring to ethical caring involving moral conflicts between personal aspirations and family responsibilities; (2) tension between justice ethics emphasizing fair distribution of responsibilities and care ethics prioritizing relationships and contextual responsiveness; (3) construction of caregiving mental models as obligatory pedagogy learned through direct experience and critical reflection. Laurens' slow-burn directorial approach presents emotional complexity through expressive close-ups and visual compositions reflecting family dynamics. This research contributes to integrating three analytical frameworks and provides practical implications for family caregiver support policies in Indonesia, including formal recognition of informal caregiving burden, culturally sensitive intervention programs, and moral education integrating care values.